A non-redundant dataset of inter-residue lysine-lysine solvent accessible surface distances in homo-oligomeric protein complexes - Gaber, Aljaž (Data Brief, 2019)
This article contains inter-residue solvent accessible surface distances between lysines in a comprehensive dataset homo-oligomeric protein complex structures, downloaded from 3D Complex database. Solvent Accessible Surface Distances were calculated with Jwalk algorithm. To avoid unnecessary redundancy due to symmetry, we calculated only distances originating from the first subunit of each protein complex. Redundancy was further reduced by including only the shortest of the two possible inter-subunit alternatives in the final non-redundant dataset. For each protein complexes we also calculated weight ob subunits, number of lysines radius of gyration and average distances. This data can be used for structural analyses of homo-oligomeric protein complexes and for further optimization of distance-based restraints, such as those based on data obtained from chemical cross-linking coupled with mass spectrometry.